Case Report: Exceptional Response to Nivolumab Plus Ipilimumab in a Young Woman With TFE3-SFPQ Fusion Translocation-Associated Renal Cell Carcinoma - Martini, Dylan J.; Jansen, Caroline S.; Harik, Lara R.; Evans, Sean T.; Olsen, T. Anders; Master, Viraj A.; Kissick, Haydn T.; Bilen, Mehmet Asim (Frontiers in Oncology, 2021)
Translocation-associated renal cell carcinoma (tRCC) is a rare, aggressive malignancy that primarily affects children and young adults. There is no clear consensus on the most effective treatment for tRCC and there are no biomarkers of response to treatments in these patients. We present a case of a 23 year-old female with metastatic tRCC to the lungs who was started on treatment with nivolumab and ipilimumab. She had a complete radiographic response to treatment and has been progression-free for over 18 months. Immunofluorescence imaging performed on the baseline primary tumor sample showed significant intratumoral immune infiltration. Importantly, these cells are present in niches characterized by TCF1+ CD8+ T cells. Histopathologic investigation showed the presence of lymphocytes in the fibrovascular septae and foci of lymphovascular invasion. Furthermore, lymphovascular invasion and intratumor niches with TCF1+ CD8+ T cells may predict a favorable response to treatment with nivolumab and ipilimumab. These findings have significant clinical relevance given that immune checkpoint inhibitors are approved for several malignancies and predictive biomarkers for response to treatment are lacking. Importantly, the identification of these TCF1+ CD8+ T cells may guide treatment for patients with tRCC, which is a rare malignancy without a consensus first-line treatment option.